Oxidative stress caused by 3-monochloro-1,2-propanediol provokes intestinal stem cell hyperproliferation and the protective role of quercetin - Zongzhong Liu; Yanfei He; Yuhan Wang; Kefeng Ren; Pengpeng Xia; Binbin Xie; Tian Wei (Ecotoxicology and Environmental Safety, 2025)
Recently, the contaminant 3-monochloropropane-1,2-diol (3-MCPD) found in food and the environment has garnered significant global attention due to its detrimental health effects on animals, including reproductive toxicity, neurotoxicity, and nephrotoxicity. However, the specific impacts and mechanisms of 3-MCPD on intestinal health remain elusive. Here, we employed the adult intestine of Drosophila melanogaster, a notable invertebrate model organism, to investigate the intestinal toxicity of 3-MCPD and its underlying mechanisms. Our findings revealed that exposure to 3-MCPD led to a decrease in the number of enterocyte cells and an elevation in apoptosis levels, ultimately disrupting the intestinal epithelial barrier and its function. This disruption subsequently triggered hyperproliferation and differentiation of intestinal stem cells (ISCs). Mechanistically, 3-MCPD induced oxidative stress in the Drosophila intestine, which was likely responsible for ISC hyperproliferation and intestinal damage. Intriguingly, quercetin, a natural antioxidant derived from dietary fruits and vegetables, alleviated 3-MCPD-induced intestinal toxicity by inhibiting the JNK pathway. Our findings uncover a mechanism whereby suppression of undesirable ISC hyperproliferation, caused by 3-MCPD-induced oxidative stress, maintains intestinal homeostasis, and provide a theoretical basis for exploiting quercetin, a natural antioxidant, as a dietary antidote against the intestinal hazards posed by environmental toxicants.